Cultivation of Pleurotus ostreatus using supplemented spent oyster Mushroom substrate - Pardo-Giménez, A.; Picornell Buendía, M. R.; De Juan Valero, J. A.; Pardo-González, J. E.; Cunha Zied, D. [UNESP]; De Cogumelos, Módulo [UNESP] (My University, 2012)
Spent Agaricus and Pleurotus substrates are mainly used as components of amendments and growing substrates, but not in sufficient quantities to solve the problem of their accumulation in mushroom producing areas, where they represent a potential pollution risk. The mushroom growing sector in Spain generates about 5105 t of spent compost, while the EU, as a whole, produces more than 3.5106 t. Among alternative management applications, it is possible to reuse these wastes in the cultivation of mushrooms, as a casing material for growing Agaricus spp. and as substrate for growing other species. In this work, the application of commercial nutritional supplements (Calprozime, Champfood and Promycel), widely used in Agaricus cultivation, is evaluated for its possible use as additive to substrates, based on spent oyster mushroom substrate (SMS), for the cultivation of Pleurotus ostreatus. Using a mixture of straw and SMS (1:1, w/w) as base material, the addition of CaSO4 (50 g kg-1) and CaCO3 (10 g kg-1) and the above supplements at 20 g kg-1 brought about a remarkable increase in production compared with the substrate without any supplement. The biological efficiencies did not differ significantly from that obtained when a commercial substrate was used as control, reaching values of 48.9 kg/100 kg substrate (dry matter) when Calprozime was used as supplement. Sporophores harvested from the supplemented substrates presented a higher dry matter content than those obtained from both commercial and non-supplemented substrates. SMS is cheap and easily available; it can be integrated into new formulations with the added advantages of lowering production costs, limiting growers' dependence on straw, and decreasing the environmental impact of its ever-growing accumulation.
Keywords: Edible mushrooms; Reuse; Sporophore quality; Valorisation; Yield; Agaricus; Basidiomycota; Pleurotus; Pleurotus ostreatus